Sambandet mellan vattenflöde och täthet av lax- och öringsyngel i Gullspångsälven : Vilka åtgärder med avseende på vattenflödet kan stärka populationen? - Björn, Malin (Karlstads universitet, Institutionen för miljö- och livsvetenskaper, 2017)
Hydropower is a renewable energy source that can be regulated when needed, but it creates barriers in rivers and causes hydrological changes in water flow. This reduces biodiversity and prevents migratory fish from completing their lifecycle. This threat from humans has reduced salmon populations worldwide. The rate of water flow can affect smolt production, and this will be investigated in this report for Atlantic salmon and Borwn trout in the river Gullspångsälven. In addition, I will suggesting which measures should be prioritized to sstabilize the population. The flow in the river Gullspångsälven is regulated by the hydropower plant at Gullspång. A correlation between the density of salmon and trout and water flow in januari, when waterflow is high, May, when the salmonids swim up from their spawning gravel and august, when waterflow is low. I found no distinct trend between the waterflow and density in the river. There were significant differences for salmon in January and May. This result may be due to species-specific properties that are influenced different by water flow or in Gullspångsälven there is a short-term regulation that probably affects salmon and trout populations negatively.